Risk management in carbon capture and geological storage: insights from a structured expert elicitation - Larkin, Patricia; Gracie, Robert; Shafiei, Ali; Dusseault, Maurice; Sarkarfarshi, Mirhamed; Aspinall, Willy; Krewski, Daniel (Université d'Ottawa | University of Ottawa, 2019)
With a focus on risk management (RM) in injection and storage for carbon capture and geological sequestration (CCS), an expert elicitation of scientific judgements quantified collective uncertainty ranges for a number of difficult environmental and human health risk challenges. Results suggest similarities and differences in opinions, an outcome that may be reflective of both the newness and the complexity of this technology. A suitable monitoring period was estimated at about a century; however, uncertainty was three orders of magnitude, with an upper (5th percentile) value of almost 1,000 years. For selected low probability high impact georisks, only site selection and monitoring were considered ‘very’ effective RM options. Monitoring, well integrity studies, emergency response plan, automatic emergency shut down system and training were considered ‘very’ or ‘extremely’ effective in managing two risks more directly related to human health. Experts responded with a wide uncertainty spread for a regulated threshold of minor, major and catastrophic leakage. A companion paper discusses elicitation findings for issues related to risk assessment.
Keywords: carbon capture and storage; expert elicitation; geological sequestration; risk management